2015
DOI: 10.1007/s11357-015-9784-y
|View full text |Cite
|
Sign up to set email alerts
|

Strength training-induced responses in older adults: attenuation of descending neural drive with age

Abstract: Although reductions in resting H-reflex responses and maximal firing frequency suggest that reduced efferent drive may limit muscle strength in elderly, there are currently no reports of V-wave measurements in elderly, reflecting the magnitude of efferent output to the muscle during maximal contraction. Furthermore, it is uncertain whether potential age-related neural deficiencies can be restored by resistance training. We assessed evoked reflex recordings in the triceps surae muscles during rest and maximal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
44
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 77 publications
4
44
1
1
Order By: Relevance
“…However, it should be noted that a recent meta-analysis concluded that flywheel resistance training was not superior to constant load strength training for increases in strength (Vicens-Bordas et al 2018), which is in line with the present results. In the present study, leg press was chosen because of its functional relevance and previously well-documented FGC improvements (Fimland et al 2009;Unhjem et al 2015), and particular care was taken to ensure a progressive increase in concentric intensity (~90% of 1RM) throughout the training period, by adding more resistance when the participants could lift more than the intended four repetitions. Importantly, previous studies have documented that short (Fimland et al 2009) and long-term (Unhjem et al 2016b) leg press/squat strength training appears to be mirrored in the plantar flexors, likely because adaptations in the central motor pathway are manifested throughout the lower extremities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that a recent meta-analysis concluded that flywheel resistance training was not superior to constant load strength training for increases in strength (Vicens-Bordas et al 2018), which is in line with the present results. In the present study, leg press was chosen because of its functional relevance and previously well-documented FGC improvements (Fimland et al 2009;Unhjem et al 2015), and particular care was taken to ensure a progressive increase in concentric intensity (~90% of 1RM) throughout the training period, by adding more resistance when the participants could lift more than the intended four repetitions. Importantly, previous studies have documented that short (Fimland et al 2009) and long-term (Unhjem et al 2016b) leg press/squat strength training appears to be mirrored in the plantar flexors, likely because adaptations in the central motor pathway are manifested throughout the lower extremities.…”
Section: Discussionmentioning
confidence: 99%
“…Third, from a purely practical standpoint, MST is simpler to administer since no or extra personnel or special equipment is required to add and remove the excess weight in the eccentric phase. Finally, of clinical importance, MST has been documented to be feasible and safe to carry out in elderly and a wide range of frail patient populations (Hoff et al 2007;Toien et al 2018;Unhjem et al 2015Unhjem et al , 2016aWang et al 2017) and contribute to improved function and ability to maintain independence in daily activities (Unhjem et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Rate of force development is influenced by neural drive, muscle-tendon stiffness and muscle fiber type (particularly fast muscle fiber) 15,27) . Unhjem et al 26) found differences between older adults and young adults with training at 75-80% of 1RM intensity, and older adults exhibited substantial improvements in RFD (0-30 ms: 40.7%, 0-50 ms: 37.7%, 0-100 ms: 38.1%, 0-200 ms: 36.3%), and MVC (20.2%). In particular, RFD increased about two times more than MVC in all time periods.…”
Section: Discussionmentioning
confidence: 98%
“…Rate of force development is influential in age-related neuromuscular activation, physical activity and fall risk 6,26) . Therefore, in relation to age-related changes in muscle force characteristics, improvement of RFD is an important training factor in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise programs show to be highly variable regarding type and mode of exercise offered [113] and result in low quality of evidence when summarized in a systematic review and meta-analysis [114]. Strength training for example, an exercise mode often used to treat sarcopenia, may not always be effective because it is not able to overcome the age-related blunted efferent neural drive plasticity [115]. This is independent from gains in force-generating capacity of the muscles seen when young and older master athletes are compared.…”
Section: Discussionmentioning
confidence: 99%